Identification of Podosphaera xanthii causing powdery mildew on sesame (Sesamum indicum L.): IDENTIFICATION OF PODOSPHAERA XANTHII CAUSING POWDERY MILDEW ON SESAME - M SUJATHA,; PRASHANT KUMAR SONI,; J JAWAHARLAL, (Journal of Oilseeds Research, 2015)
Powderymildew is one ofthe severe diseases on sesame (Sesamum indicum L.) causing high yield loss. It occurs on epidemic scale during flowering and post flowering stages under favourable weather conditions of high humidity and lownight temperature. In contrary, one accession ofsesame (Tripura local) fromMeghalaya was heavily infected with powdery mildew during peak summer of 2015. Microscopic analysis of the anamorph and molecular characterization using ITS primers specific to the powdery mildew confirmed the causal organism. Use of species specific ITS primers resulted in a 454 bp amplicon specific to Podosphaera. Blast analysis of the sequence showed highest similarity with Podosphaera xanthii confirming the pathogen.